638 Sleep and circadian markers of BMI in a diverse sample of 9-year old children from the Fragile Families Child and Wellbeing Study. (3rd May 2021) - Chung, Alicia; Moore, Jesse; Jin, Peng; Nunes, Joao; Jean-Louis, Giardin; Seixas, Azizi
Abstract: Introduction: Hispanic and Black school-age children from low-income communities experience disproportionate rates of obesity (26% Hispanic, 22% Black) compared to their White counterparts (14%). Sleep patterns and circadian regulation of biological markers are associated with BMI status. However, little is known about racial and ethnic disparities in circadian regulation among children of color. These suggest that it is important to investigate biological markers that could help delineate associations between sleep-circadian regulation and obesity among children of color. Serotonin transporter gene, a neurotransmitter associated with circadian rhythm regulation, has emerged as an important biological variable. In this study, we investigated whether this factor could serve as a proxy for studying associations of circadian rhythm regulation with weight status in this diverse sample. Methods: Statistical analysis included descriptive and linear regression analysis of the wave 5, Year 9 cohort of the Fragile Families Child and Wellbeing Study dataset. Interviews were conducted with the participant child around their ninth birthday for data collection on home routines and other parent relationship and school connectedness variables. Biological variables were derived from saliva samples at Year 9 to assess telomere length and DNA methylation levels and changes. Variables of interest included sleep duration, sleep timing, and biological variables 5httlpr (insomnia and sleep quality), skin 2 (serotonin transporter), telomere length (stress) and rs9939609 (fat mass and obesity), with BMI as the outcome. Results: The final sample of 466 children comprised 52% male were 9 years old. Participants' race was: 35% White, 46% Black, 20% Hispanic, 4% Asian and 5% other. Median family income was 42, 500. Sleep duration obtained from these children was negatively associated with BMI (β = -0.245 with p=0.022). We found that gk5stin212 (serotonin transporter gene) was positively associated with BMI (β = 0.991, p = 0.009), while no significant associations was found for genetic variable gk5stin210. Conclusion: Circadian rhythm dysregulation may serve as a biological mechanism driving overweight or obesity among minority children. Lifestyle and behavioral interventions aimed at the family unit may be needed to modify household and environmental factors that affect circadian regulation among children. Support (if any): NIH (T32HL129953), K07AG052685, R01MD007716, R01HL142066, K01HL135452, R01HL152453